El reconocimiento de la persona en el trabajo profesional del informador - Atarama Rojas, Tomás (Mercurio Peruano, 2020)
What is held here is that the social communicator or professional of media will be able to adequately carry out his work if he is aware that his activity is at the service of someone. To achieve this objective, we emphasize that the public cannot be considered as a homogeneous mass of individuals. By understanding the public as a group of real people, the activity of the journalist acquires an unsuspected relevance: in many cases, the vital orientation of each man and woman, and therefore of the community, depends on our work.